Majority of NCAA Div. 1 football players at specific institute show patellar tendon blood flow post-exercise - Schaugaard, B. T.; Hinkle, L. J; Davidson, G.; Mortensen, B. B.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
Patellar tendinopathy is a frequent overuse injury among collegiate athletes, especially in football players, due to the intense strain on the patellar tendon. Power Doppler Imaging (PDI) is an effective way to analyze blood flow (BF) within the tendon and correlates to patellar tendinopathy and pain. A healthy and normal tendon should have a score of 0 on the Arias scale.